The relationship between birth months and physical fitness performance among young athletes in east coast Malaysia / Nik Intan Kamilin Nik Hel - Nik Hel, Nik Intan Kamilin (Faculty of Sport Science and Recreation, 2015)
The purpose of this study is to compare and verify the relationship between birth months and physical fitness ability of young athletes in East Coast Malaysia. There were 111 subject aged 12 years old participated for this study which comes from all district of East Coast Malaysia. The subjects were divided into three quarter or three groups which is 35 of them are in quarter 1.The quarter 1 or also known as early-year birth babies or young athletes are from January to April. Meanwhile, 35 subjects from 111 subjects are in quarter 2 or May to August group and the last one-is quarter 3 which consist 41 subjects and they are end-year birth which is September to December. All of subjects were tested at Kompleks Terbuka, Kompleks Belia dan Sukan Panji, Kota Bharu, Kelantan. The physical fitness of subject was divided into anthropometric, aerobic and anaerobic test which is consisted of height measurement, weight and sitting height. Besides, for anaerobic test or exercise, the tests are arm span, sit and reach, hand grip strength and standing broad jump test. Next, for the aerobic test, there are shuttle run, Yoyo test, and 40m speed. One shot data study design was used for this study, subject performed test only on one occasion and the data was recorded. Descriptive statistic was used to describe physical fitness profile and ANOVA analysis is to compare mean differences of fitness level of three quarter birth month of young athletes in East Coast Malaysia